VOCs (Volatile Organic Compounds) Concentration Measurement in Human-Exhaled Breath - A Preliminary Study: Measurement of VOC Levels in Human-Exhaled Breath - Hadi, Kasnawi Al; Budianto, Arif; Alhadawiah, Sabila; Fidya, Karina Alma; Rahayu, Satutik (JURNAL SAINS TEKNOLOGI & LINGKUNGAN, 2024)
VOC is a group of organic compounds that easily evaporate into the atmosphere and have various impacts on human health and the environment. Human exhaled breath and VOC is related to each other. The concentration of VOC differs from an abnormal condition to other abnormalities. However, there is limited information or study about VOC concentration in human exhaled breath. In line with this, this study aims to develop a VOC meter or a measurement system using a CCS811 sensor for human exhaled breath. This study used a CCS811 sensor, a microcontroller, and a suction pump installed inside a sensor box. The system was calibrated using filtered and non-filtered air. The system was tested using varying flow rates. At the final test, the system was tested to measure VOC levels in human exhaled breaths. The results show that the VOC measurement system can measure VOC levels in different air conditions for both filtered and non-filtered air. The use of different flow rates influences the system's performance. The highest sensitivity level is obtained at 0.7 m/s of the flow rate of the suction pump. The system was also able to measure VOC concentrations of the human exhaled breath with concentrations of 0 ppb to 1156 ppb. The VOC concentrations of human exhaled breath depend on many factors that should be further analyzed, including the medical treatment history, food consumption, placebo effect, and many other parameters.